Faktor-Faktor Yang Mempengaruhi Initial Return Pada Saat IPO Di Bursa Efek Indonesia Periode Tahun 2006-2015 - Rini Tri Astuti (Jurnal Ekonomi, 2017)
The purpose of this empirical study is to analyze the effect of accounting information and non-accounting information to initial return infirm that do Initial Public Offering (IPO) and listing on Indonesia Stock Exchange in 2006-2015. The population in this research are the firms that do Initial Public Offering (IPO) in 2006-2015. With the purposive sampling method from 210 firms, 143 firms meet the criteria of the sample. The result of regression analysis shows that accounting information Return On Asset (ROA) and firm size, and also non-accounting information auditor reputation individually had a significant effect to initial return, while accounting information Earning Per Share (EPS) and financial leverage, and also non-accounting information firm age, underwriter reputation and type of industry had no significant effect on initial return individually.